Strategi Pengelolaan Modal Kerja untuk Meningkatkan Kualitas Laporan Keuangan pada Rumah Sakit Umum Daerah (Studi Kasus pada RSUD BLUD di Wilayah Purwasuka Jawa Barat) - Lusiana Badriah Hartono; Azhar Affandi; Dadang Suwanda (Universitas Batanghari Jambi, 2023)
The management of working capital in the functional budget of RSUD BLUD deals with current assets and current debt of the hospital, one of the most important aspects of spending on hospital operational costs. The purpose of this study was to determine how the management of working capital on the functional budget at RSUD BLUD, starting from planning and budgeting, implementation of budget realization of revenue, expenditure realization and administration as well as reporting and accountability, which has an impact on financial statements. The research approach used is qualitative analysis and the nature of the research is a single case study, with the locus of research at the BLUD RSUD in the Purwasuka Region of West Java, at Bayu Asih Hospital Purwakarta Regency, Subang Regional Hospital and Karawang Regional Hospital. The results showed that working capital management was not optimal due to various obstacles faced by RSUD BLUD in planning and budgeting, revenue and expenditure, regulation, competence of financial human resources, availability of data and financial systems/applications and financial quality achievements. Therefore, a working capital management strategy is needed so that the quality of hospital financial reports is getting better with strategies in planning BLUD RSUD budgeting; Optimizing BLUD RSUD revenue; Effective and efficient spending; Strengthening the latest BLUD RSUD regulations; Financial HR competencies; Data and implementation of financial systems/applications. So that the financial statements of RSUD BLUD can be maintained in good quality and accountable.